Digital Transaction Factors and Benefit : Based on the Immanuel Kant’s Philosophy - Rika Rahayu; Maridha Permatasari; Aulia Rahmadini (Politeknik Negeri Madiun, 2023)
The business world continuously changes due to technological developments. This change is in line with Immanuel Kant's philosophy that knowledge is something that has no boundaries. This study aims to identify the factors affecting the preferences and perceived benefits of using digital payments based on Immanuel Kant's philosophy. This study used a literature review method using online journal databases and other information to obtain relevant literature from previous studies. The results of the study showed that this change was in line with Immanuel Kant's philosophy regarding knowledge that humans will never reach the end of the journey but only continuously expand their horizons. Then, each change has determination factors, and the process of change results in benefits. In this digital era, people can adapt to transaction developments and also apply them. This is in line with Immanuel Kant's philosophy that every aspect of life experiences a dynamic or continuous change. Therefore, service providers or the community have to have adequate competence.